Enterprise Mac Managed Preferences - Marczak, Edward; Neagle, Greg (Apress : Imprint: Apress, 2010)
Many systems administrators on the Mac need a way to manage machine configuration after initial setup and deployment. Apple's Managed Preferences system (also known as MCX) is under-documented, often misunderstood, and sometimes outright unknown by systems administrators. MCX is usually deployed in conjunction with an OS X server, but it can also be used in Windows environments or where no dedicated server exists at all. Enterprise Mac Managed Preferences is the definitive guide to Apple's Managed Client technology. With this book, you'll get the following: An example-driven guide to Mac OS X Managed Preferences/Client technology Recipes for common use case studies and patterns A targeted approach appropriate for any sys admin that manages Macs in an OS X or Windows environment This is the only book that focuses on this facet of OS X exclusively. If you're a sys admin, this book will take away much of the pain of working with OS X client systems. Even better, both of the authors are very involved in the Mac community-Greg Neagle is part of the MacEnterprise steering committee, and Ed Marczak is the executive editor and an author for MacTech magazine and a member of the Apple Consultants Network.